2023
DOI: 10.1021/acs.langmuir.2c02651
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interfacial Hydroxylation Microstructure on Quartz Flotation by Sodium Oleate

Abstract: Quartz, a common inorganic nonmetallic mineral, is usually removed or purified by beneficiation, normally flotation. Given the strong polarity of the quartz surface, it is easy to hydrate to form a hydroxylation layer, which makes it impossible to float quartz with sodium oleate (OL) used alone. An ideal flotation method for quartz is preactivation with Ca2+, followed by collection with OL. Herein, the effects of surface hydroxylation on the adsorption of the anionic collector OL on the quartz surface before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In addition, it is worth mentioning that the presence of numerous hydroxyls disrupts the electrical neutrality of the periodic system, and here, we use the counterion H anions to retain the charge balance of the system. Considering that the presence of numerous counterions in the system can cause difficulties in DFT calculations, the treatment was that the practice of placing the counterions at the bottom of the slab was adopted, allowing them to relax to the unsaturated coordinated anions . This avoids the interaction of numerous counterions with the adsorbate in the finite vacuum box, which may lead to a large error in the calculated adsorption energy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is worth mentioning that the presence of numerous hydroxyls disrupts the electrical neutrality of the periodic system, and here, we use the counterion H anions to retain the charge balance of the system. Considering that the presence of numerous counterions in the system can cause difficulties in DFT calculations, the treatment was that the practice of placing the counterions at the bottom of the slab was adopted, allowing them to relax to the unsaturated coordinated anions . This avoids the interaction of numerous counterions with the adsorbate in the finite vacuum box, which may lead to a large error in the calculated adsorption energy.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that the presence of numerous counterions in the system can cause difficulties in DFT calculations, the treatment was that the practice of placing the counterions at the bottom of the slab was adopted, allowing them to relax to the unsaturated coordinated anions. 33 This avoids the interaction of numerous counterions with the adsorbate in the finite vacuum box, which may lead to a large error in the calculated adsorption energy.…”
Section: Adsorption Thermodynamic Evaluationmentioning
confidence: 99%
“…Quartz surface activation with Ca 2+ or Ca­(OH) + repels water molecules from the surface, bridging α-BLA – to it and leading to a significant promotion of quartz floatability. DFT calculations further revealed that the preactivation of hydroxylated quartz surface with Ca 2+ introduces favorable active sites for subsequent adsorption of sodium oleate, making direct flotation of quartz industrially feasible …”
Section: Applications Of Molecular Modeling To Froth Flotationmentioning
confidence: 99%
“…DFT calculations further revealed that the preactivation of hydroxylated quartz surface with Ca 2+ introduces favorable active sites for subsequent adsorption of sodium oleate, making direct flotation of quartz industrially feasible. 351 MD simulations based on the Universal force field parameters and Mulliken partial charges were conducted to assess the hydrophilicity of Cu 2+ activated sphalerite surface. 352 The wettability of the pristine and the Cu 2+ -activated sphalerite was compared by calculating the contact angle, water number density distribution, water dipole orientation, and water residence time, among other things.…”
Section: Mineral Surface Modification and Activation In Flotationmentioning
confidence: 99%
“…15 For the Ca 2+ -activated quartz anion flotation process, two possible mechanisms have been reported by Zhang et al through first-principles calculations. 16 One process is the preadsorption of Ca 2+ ions on the quartz surface, which offers reaction sites for the NaOL anion collector's subsequent interfacial adsorption. The other mechanism is that the NaOL anion collector preassembles with Ca 2+ ions to form a calcium dioleate colloidal precipitate and works on the mineral surface to achieve hydrophobic floating of quartz.…”
Section: Introductionmentioning
confidence: 99%